RESEARCH FOR BLOW PRESSURE IMPACT ON THE DYNAMIC CHARACTERISTICS OF LIQUID-AIR HAMMER BASED ON MATLAB - XIE Miao; JIA Can; MAO Jun; XU Chang (Jixie qiangdu)
Blow pressure is the key factor to influence the dynamic characteristics of liquid-air hammer,in order to improving control accuracy of the forging equipment,liquid-air hammer was regard as research object,established liquid-air hammer blow process stages of non-plastic deformation and plastic deformation of Lagrange dynamics model,using the Matlab/Simulink numerical simulation to analyze movement regularity of liquid-air hammer blow process,researched for blow pressure impact on the dynamic characteristics of liquid-air hammer,provided the theoretical basis for the equipment later debugging in order to achieve the purpose of precise control.The field experiment results show that the control system can meet the requirements of liquid-air hammer precision blow process.